A Review of Wearing a Mask and How to Correctly Wear it in Shahroud City - Garkaz , Omid; Zirouhi , Atefeh; Mohammadi , Faezeh; Yavari , Ghazaleh; Damghani , Zohreh (Shahroud Journal of Medical Sciences, 2021)
Background: One of the most important issues since SARS-CoV-2 was identified was the growing information on how the virus was transmitted and how to protect against it. However, many key questions have not yet been fully answered. This study aimed to investigate the correct wearing of a mask in Shahroud city.Methods: This study was a descriptive cross-sectional one conducted on 800 people in Shahroud city in a two-month interval (Aug. 22, 2020, to October 30, 2020). Data were collected using a checklist including demographic information. After being collected, the data were entered into SPSS18 and analyzed using descriptive statistics.Results: The results indicated that out of 800 people taking part, 415 people (51.9%) were male and 385 ones (48.1%) were female. The mean participants’ age was 61.78 16±16.09; most participants in the study were born in the year 1972-1995 with 385 ones (48%). Also, concerning masks, it was found that the use of masks and the correct use of them accounted for 528 cases (66%) and 377 cases (47.1%), respectively. The most used mask was a surgical mask with 343 cases (42.9). Concerning the non-use of a mask, 132 people (16.5%) cited choking as the most important reason for not wearing a mask. Also, 681 people (85.1%) and 557 ones (69.6%) had chosen not to participate at weddings and parties, respectively.Conclusions: The results suggested that a greater percentage of participants in the study knew how to correctly wear a mask while not having a history of participating in ceremonies and parties, which is a very good issue.Keywords: Mask, Correct wearing, Shahroud